Effects of customized vestibular rehabilitation on static balance among adults with benign paroxysmal positional vertigo - Phui Lin Se To; Devinder Kaur Ajit Singh; Nor Haniza Abdul Wahat; Marniza Omar; Whitney, S.L. (Penerbit Universiti Kebangsaan Malaysia, 2022)
The aim of this study was to detemine the effectiveness of Customized vestibular rehabilitation (CVR) in addition to the standard Canalith repositioning maneuver (CRM) on static balance among adults with posterior canal Benign Paroxysmal Positional Vertigo (BPPV). In this randomised controlled trial, 28 adults with idiopathic unilateral posterior canal BPPV were randomized to either the control or experimental group. The experimental group (n=14, mean age: 50.71±9.88 years) received CVR in addition to CRM, and the control group (n=14, mean age: 54.36±8.55 years) received only CRM for 6 weeks. Measurements of static balance (postural sway) using a portable kinematic sensor were performed at baseline, four and six weeks after treatment for both groups while standing on firm and foam surface with eyes open (EO) and closed (EC). Only standing on foam surface with EC was observed to have a significant interaction effect, F (2, 52) =5.28, p<0.05. This suggest that the groups were affected differently by the intervention and greater improvement was demonstrated in the experimental group. Post hoc test showed that a significant difference (p<0.05) in static balance was shown between baseline and 6th week after intervention. The results of our study indicate that CVR in addition to CRM improved static balance in adults with UPC BPPV at 6th week after intervention for persons with BPPV.